Faktor-Faktor Penghambat Penyaluran Dana Desa - Mahbub Ulhaq (Jurnal Ilmiah Universitas Batanghari Jambi, 2022)
This study analyzes the implementation of the Village Fund Program and the cause of the delay in Disbursement of the fund in 2021 in Musi Rawas. The Village Community Empowerment Service (DPMD) was investigated along with The Government Finance and Asset Management Office. The research method is descriptive qualitative analysis, with data collected by conducting interviews and collecting documentation. The results reveal that the delay in disbursement was caused by some factors such as administration, system, and human resources.